Identify risk factors for perioperative outcomes in Intracorporeal Urinary Diversion and Extracorporeal Urinary Diversion with Robotic Cystectomy - Hangcheng Fu; Laura Davis; Venkat Ramakrishnan; Thomas Barefoot; Colleen Sholtes; Lifan Liang; Mohammed Said; Jamie Messer (International Brazilian Journal of Urology, 2024)
ABSTRACT Introduction: The increasing adoption of robotic-assisted cystectomy with intracorporeal urinary diversion (ICUD), despite its complexity, prompts a detailed comparison with extracorporeal urinary diversion (ECUD). Our study at a single institution investigates perioperative outcomes and identifies risk factors impacting the success of these surgical approaches. Methods: In this retrospective analysis, 174 patients who underwent robotic-assisted cystectomy at the University of Louisville from June 2016 to August 2021 were reviewed. The cohort was divided into two groups based on the urinary diversion method: 30 patients underwent ECUD and 144 underwent ICUD. Data on demographics, complication rates, length of hospital stay, and readmission rates were meticulously collected and analyzed. Results: Operative times were comparable between the ICUD and ECUD groups. However, the ICUD group had a significantly lower intraoperative transfusion rate (0.5 vs. 1.0, p=0.02) and shorter hospital stay (7.8 vs. 12.3 days, p<0.001). Factors such as male sex, smoking history, diabetes mellitus, intravesical therapy, higher ASA, and ACCI scores were associated with increased Clavien-Dindo Grade 3 or higher complications. Age over 70 was the sole factor linked to a higher 90-day readmission rate, with no specific characteristics influencing the 30-day rate. Conclusion: Robotic cystectomy with ICUD results in shorter hospitalizations and lower intraoperative transfusion rates compared to ECUD, without differences in operative time, high-grade postoperative complications, or readmission rates. These findings can inform clinical decision-making, highlighting ICUD as a potentially more favorable option in appropriate settings.